Coaction of individual and environmental factors: a review of intensive therapy paradigms for children with unilateral spastic cerebral palsy. (27th July 2017) - Ferre, Claudio L; Gordon, Andrew M
Abstract : Evidence‐based treatment approaches for children with unilateral spastic cerebral palsy are expanding and being modified to fit the constraints of families and the child receiving treatment. In this review, we first provide an overview of a theoretical framework that considers the intricate interactions between the individual child and the environment in which treatment is provided. Next, we describe intensive interventions that have strong support for their efficacy. We also highlight the heterogeneity with which children respond to these approaches. Individual characteristics that might affect responsiveness are summarized. We propose that a one‐size‐fits‐all approach may not be as efficacious as approaches based on the specific brain damage and resulting development of the corticospinal tract. Finally, we review evidence suggesting that the environment can be structured to promote opportunities for intensive practice and self‐generated movement—two important aspects of efficacious treatments. Emphasis is placed on intensive home programs delivered by caregivers. What this paper adds: Considerable variability exists in how children with unilateral spastic cerebral palsy respond to intensive upper extremity therapies. Individual and environmental factors interact to shape responsiveness. What this paper adds: Considerable variability exists in how children with unilateral spastic cerebral palsy respond to intensive upper extremity therapies. Individual and environmental factors interact to shape responsiveness. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.